Pelatihan Pembuatan Marka Jalan Lingkungan di Desa Kuok - islah, muhammad; Febryanto; Lelis Febrianty, Nanda (Journal of Social and Community Service, 2025)
This community service activity was carried out in Kuok Village, Kuok District, Kampar Regency with the aim of providing training on making environmental road markings. The main problem faced by the partners was the community's lack of understanding regarding techniques, standards, and regulations in making road markings, as well as limited supporting facilities. The implementation method of the activity included socialization, counseling, and direct practice of making road markings by involving village officials, the community, and students. The results of the activity showed an increase in community knowledge regarding the function and importance of road markings for traffic safety, as well as practical skills in the process of making them. In addition, active community participation in this activity fostered a sense of ownership and collective awareness of the importance of road infrastructure maintenance in the village environment. This activity is expected to become a model of community empowerment that can be applied in other areas, while strengthening the implementation of the Tri Dharma of Higher Education through real contributions to village development.